A Study Of Employees' Motivation In Manufacturing Organization - Tan, , Kiam Min (2006)
The purpose of this study is to uncover the impact of commonly perceived driving factors on motivation level of employees in manufacturing organization. The scope of the study focuses on a total of eleven factors ( Patricia Huddleston & Linda K. Good, 1999) - Pay, self-satisfaction, skill development, job security, learning, promotion, accomplishment , freedom, respect, praise and friendliness that influence on employees' motivation level.